One-Screw Fixation Provides Similar Stability to That of Two-Screw Fixation for Type II Dens Fractures - Feng, Gang (Springer-Verlag, 2012)
BACKGROUND: Anterior screw fixation has been widely adopted for the treatment of Type II dens fractures. However, there is still controversy regarding whether one- or two-screw fixation is more appropriate. QUESTIONS/PURPOSES: We addressed three questions: (1) Do one- and two-screw fixation techniques differ regarding shear stiffness and rotational stiffness? (2) Can shear stiffness and rotational stiffness after screw fixation be restored to normal? (3) Does stiffness after screw fixation correlate with bone mineral density (BMD)? METHODS: We randomly assigned 14 fresh axes into two groups (seven axes each): one receiving one-screw fixation and another receiving two-screw fixation. Shear and torsional stiffness were measured using a nondestructive low-load test in six directions. A transverse osteotomy then was created at the base of the dens and fixed using one or two screws. Shear and torsional stiffness were tested again under the same testing conditions. RESULTS: Mean stiffness in all directions after screw fixation was similar in both groups. The stiffness after one- and two-screw fixation was not restored to normal: the mean shear stiffness restored ratio was less than 50% and the mean torsional stiffness restored ratio was less than 6% in both groups. BMD did not correlate with mean stiffness after screw fixation in both groups. CONCLUSIONS: One- and two-screw fixation for Type II dens fractures provide similar stability but neither restores normal shear or torsional stiffness. CLINICAL RELEVANCE: One-screw fixation might be used as an alternative to two-screw fixation. Assumed BMD should not influence surgical decision making.